Examining Effect of Core Capital Tier 1 on Financial Stability in Indonesia - Igamo, Alghifari Mahdi; Apriani, Deassy; Gustriani; Aini, Halia Butra (Faculty of Economics, Universitas Sriwijaya, 2025)
This research aims to examine the impact of core capital tier 1 (CCT), loan to deposit ratio (LDR), leverage ratio (LR), interconnection ratio (INR) and on stability financial that measured from credit growth rate (CGR) in Indonesia. Data in this study used secondary data with a time series of Jan 2012–Dec 2022 using the Vector Error Correction Model (VECM) method. The estimation results show that variables that have a significant relationship to financial stability in the short term are LDR and CCT variables. In long term results, there is a positive relationship between LDR and CGR. For a given level of risk, having more capital can in principle imply greater stability. Core Capital Tier 1 assess bank resilience to adverse economic situations and maintain the stability of the financial system.